A Contribution for the valorisation of sheep and goat cheese whey through nanofiltration - Macedo, Antónia Teresa Zorro Nobre (2018)
The amount of cheese whey generated from the production of speciality sheep and goat cheese is significantly growing due to the acclaimed nutritional and medicinal benefits of the milk from these species. However, most of the cheese whey generated has no applications, thus giving rise to environmental problems. This work focuses on the study of the performance of the nanofiltration process for recovering the permeates of ultrafiltration from sheep and goat cheese whey. Nanofiltration experiments were carried out with membranes of nanofiltration (NF) in total recirculation and concentration modes, at 25 C. Nanofiltration of the ultrafiltration permeates from sheep cheese whey was done at a pressure of 3.0 ⇥ 106 Pa and a circulation velocity of 1.42 m·s 1, until a volume concentration factor (VCF) of 2.5. Nanofiltration of the permeates from ultrafiltration of goat cheese whey was performed at a pressure of 2.0 ⇥ 106 Pa and a circulation velocity of 0.94 m·s 1, until a VCF of 2.0. From the results, it was concluded that osmotic pressure was the most important factor affecting the performance of the process. In both cases, the final permeates had a much lower organic load and its future use in the process of cheese making should be evaluated.